Paris spring - Naughtie, James, 1951- (Overlook Press, 2017)
Paris in 1968 - seething with revolutionaries and spies - sees Will Flemyng's world turned upside down after a mysterious encounter on the metro and a chance revelation from a rival operative. In a city alive with talk of revolution, Will finds himself in the thick of the action. But now he gets news that threatens the closest and most complicated relationship in his life -the one with his younger brother.